PI(3) kinase is associated with a mechanism of immunoresistance in breast and prostate cancer - Crane, CA (2008)
Immune escape describes a critical event whereby tumor cells adopt an immunoresistant phenotype to escape adaptive surveillance. We show that expression of a pivotal negative regulator of T-cell function, B7-H1, correlates with PI(3) kinase activation in breast and prostate cancer patients. B7-H1-mediated immunoresistance can be attenuated by inhibitors of the PI(3) kinase pathway, and is dependent on S6K1-mediated translational regulation of B7-H1 protein. Breast and prostate carcinoma cells with activated PI(3) kinase lose the immunoresistant phenotype after treatment with B7-H1 siRNA. Conversely, breast and prostate carcinoma cells with minimal PI(3) kinase activation adopt an immunoresistant phenotype when engineered to overexpress B7-H1 protein. These observations describe a mechanism for immune escape from tumor dormancy in humans that relates to oncogenesis.